"The Master Plan is a Master Killer": Land dispossession and powerful resistance in Oromia, Ethiopia. Issue 2 (1st June 2019) - Wayessa, Gutu Olana
Abstract : English abstract: Land is a key resource and an epicenter of struggle in Ethiopia, as indicated by the incident that sparked a powerful protest in Oromia in 2015. The protest quickly galvanized against the Addis Ababa Master Plan, which government officials represented as a "development plan, " while the protesters counter-framed it as a "Master Killer, " highlighting the immanent risks of land dispossession and displacement of people. This article employs a political-ecological approach to examine environmental, socio-cultural, and political-economic implications of the Master Plan and the resistance against it as a signifier of wider issues of contestation connected to land and displacement. It highlights contemporary grievances of the Oromo people in relation to unresolved historical questions and outlines the responses of the government to the protest. Spanish abstract: La tierra es un recurso clave y un epicentro de lucha en Etiopía. En el 2015 surgió una poderosa protesta en Oromia contra el Plan Maestro de Addis Abeba, presentado por el gobierno como un "plan de desarrollo", mientras que los manifestantes lo enmarcaron como un "Asesino Maestro", destacando los inminentes riesgos de la desposesión de tierras y el desplazamiento de personas. Este artículo emplea un enfoque político-ecológico para examinar las implicaciones ambientales, socioculturales y político-económicas del Plan Maestro y la resistencia en su contra como resultado de temas más amplios de disputa relacionados con la tierra y el desplazamiento. Destaca las quejas contemporáneas de la gente de Oromo en relación con preguntas históricas no resueltas y describe las respuestas del gobierno a la protesta. French abstract: La terre est une ressource clef et un motif central de conflit en Éthiopie. Les circonstances actuelles du pays accentuent cette tendance historique. En témoigne la protestation des Oromos contre le Programme Directeur d'Addis-Abeba que les fonctionnaires présentent comme un programme de développement alors que les protestataires le désignent comme "un maître-tueur", en pointant les risques de dépossession de la terre et de déplacement de populations qui lui sont inhérents. Cet article utilise une approche d'écologie politique pour examiner ses implications dans le sens d'une protestation autour de la terre et du déplacement. Il analyse le programme directeur et la protestation des Oromos dans le cadre des principes idéologiques et structurels du gouvernement, de ses politiques et de ses pratiques.